Experimental study of small scale and high expansion ratio ORC for recovering high temperature waste heat. (1st October 2020) - Uusitalo, Antti; Turunen-Saaresti, Teemu; Honkatukia, Juha; Dhanasegaran, Radheesh
Abstract: In recent times, the use and development of small-scale ( ≈ 10 kW) ORC systems has received an increasing interest. However, the operational characteristics of small-scale high-expansion ratio ORC turbines are not yet well understood. In this study, a small-scale high-temperature ORC was investigated experimentally. The studied system has a high-speed turbogenerator including a supersonic radial turbine, a permanent magnet generator and a Barske-type feed pump assembled on a single shaft. Siloxane MDM is used as the working fluid. The turbogenerator performance was studied under different operating conditions and the experimental results were compared against the results obtained from the numerical ORC cycle model for validating the numerical results. The turbine was analyzed to have the mechanical power output close to the system design value and a maximum electric power output of 6 kW was measured. The turbogenerator was capable to be operated at the targeted rotational speed range of 12 000 rpm to 31 000 rpm. Thus, the technical potential of using high rotational speed and supersonic turbomachinery in small-scale and high expansion ratio ORC applications was confirmed. The results highlights the importance of reducing turbogenerator losses and internal power consumption to reach higher power outputs in the future.